Społeczne i przestrzenne uwarunkowania potencjału innowacyjnego społeczności lokalnych - Tuziak, Bożena (Social and Spatial Conditionings of the Innovative Potential of Local Communities, 2006)
The article introduces selected aspects of social and spatial determinants of the innovative potential of the local communities. It emphasizes the importance of the web of relations and social ties as important resources in each local community, which together with the readiness to cooperate and mutual trust create the social capital essential for creating and the right functioning of modem rational economical and political institutions, and to a high degree conditioning tendency to innovations.The article also shows, on the example of the Podkarpacie district, the role of space and place understood as an environment determining producing innovations through creating local dynamic links between the companies, local administration, the business encouraging organizations, scientific - research institutions, universities, associations and public organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 655-663